Methods Of Refactoring And Optimizing Legacy Systems - Abdumannonov, Akhmadillo; Abdukadirov, Bakhtiyor (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article provides a scientific and practical analysis of refactoring and optimization processes in legacy systems. In modern software engineering, the complete replacement of outdated information systems is not always an effective solution; therefore, gradual modernization has become increasingly important. The study examines the theoretical foundations of refactoring and its impact on software architecture, code quality, modularity, and maintainability. It also analyzes optimization techniques, including improving algorithmic efficiency, selecting appropriate data structures, and optimizing memory and computational resource usage. The research results demonstrate that refactoring and optimization significantly improve the stability, performance, and scalability of legacy systems.